Myasthenia Gravis and COVID-19: Clinical Characteristics and Outcomes - Camelo-Filho, Antonio E.; Silva, André M. S.; Estephan, Eduardo P.; Zambon, Antônio A.; Mendonça, Rodrigo H.; Souza, Paulo V. S.; Pinto, Wladimir B. V. R.; Oliveira, Acary S. B.; Dangoni-Filho, Iron; Pouza, Ana F. P.; Valerio, Berenice C. O.; Zanoteli, Edmar (Frontiers in Neurology, 2020)
Myasthenia gravis (MG), an autoimmune neuromuscular disorder, may be a risk factor for severe COVID-19. We conducted an observational retrospective study with 15 consecutive adult MG patients admitted with COVID-19 at four hospitals in São Paulo, Brazil. Most patients with MG hospitalized for COVID-19 had severe courses of the disease: 87% were admitted in the intensive care unit, 73% needed mechanical ventilation, and 30% died. Immunoglobulin use and the plasma exchange procedure were safe. Immunosuppressive therapy seems to be associated with better outcomes, as it might play a protective role.